Efektivitas Penggunaan Media Youtube Untuk Meningkatkan Keterampilan Menulis Teks Ulasan Siswa Kelas Viii Smp IT Ma’arif Padangpanjang - Rifalda, Azri; Irfadila, Mimi Sri (Inovasi Pendidikan, 2025)
This research is motivated by several factors. First, students still face difficulties in writing review texts according to the structure of review texts. Second, the use of learning media has not been maximized in the learning process. Third, YouTube media has not yet been applied in teaching materials related to writing review texts. This study aims to describe the effectiveness of YouTube media in improving the review text writing skills of eighth-grade students at SMP IT Ma’arif Padangpanjang. This research is quantitative in nature, employing an experimental method with a one-group pretest-posttest design. The data collection technique was conducted in two sessions. First, a pretest of writing review texts without using YouTube media. Second, a posttest of writing review texts using YouTube media. The data analysis techniques include: (1) reading and examining the review texts written by students; (2) converting and processing the writing skill scores into grades; (3) classifying students’ review text writing skills; (4) presenting grades in the form of a frequency distribution table; (5) determining the average score of students’ review text writing skills; (6) conducting a normality test; (7) conducting a homogeneity test; (8) conducting a hypothesis test; and (9) concluding the results and discussion. The results of this study are as follows: first, the review text writing skills of eighth-grade students at SMP IT Ma’arif Padangpanjang without using YouTube media obtained an average score of 54.6, which is classified as poor. Second, the review text writing skills of the same students using YouTube media obtained an average score of 67.6, which is classified as fair. Third, there is a significant effectiveness in the use of YouTube media on students’ review text writing skills at SMP IT Ma’arif Padangpanjang, as the calculated t-value (3.896) is greater than the t-table value (1.701), thus Ho is rejected and Ha is accepted. Therefore, YouTube media is effective for use in learning review text writing. Keywords: YouTube Media, Review Text Writing